Analysis of Information Needs and Student Content Preferences on Social Media of the Sriwijaya State Polytechnic - M. Ridho Apriliadi; Alexandra Naflah Ramadhani M; Riska Talisa; Robiah Alawiyah; Yunita Fauzia Achmad; Astika Ulfah Izzati; Bangga Surya Nagara (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2026)
This study aims to analyze students' information needs and content preferences on social media of Politeknik Negeri Sriwijaya (POLSRI). Using a mixed-method approach encompassing client interviews, internal Instagram Insights data, social media observation, and direct interviews with three audiences, this study identifies the demographic, psychographic, and digital behavioral profiles of Polsri audiences. Results indicate the primary audience is aged 17-24, predominantly female (54.3%), from South Sumatra, especially Palembang (49.8%), and most active on social media between 19.00-23.00. Preferred platforms are Instagram and TikTok. Audiences need fast, transparent, and relevant content in the form of authentic and relatable short videos. Key pain points include hard-to-digest campus information and one-way communication. This study recommends a more responsive, informative, and interactive campus social media content strategy to enhance student digital engagement.